Penentu Industri Kecil Unggulan Dikabupaten Muaro Jambi Menggunakan Metode Simple Additive Weghting (SAW) - Kurniawansyah, Kevin; Marthiawati, Noneng; Yuvanda, Sesraria (Jurnal Ilmiah SINUS, 2024)
Small and Medium Industries (IKM) have an important role in economic development. Muaro Jambi Regency is one of the districts in Jambi Province whose people are engaged in small and medium industrial businesses (IKM). This is inseparable from the important role of the Muaro Jambi Regency Government in supporting the development of small and medium industries (IKM). SMEs in Muaro Jambi Regency are grouped into 5 groups, namely craft SMEs, chemical and building materials SMEs, metal and electronics SMEs, food SMEs, and clothing SMEs. Of these 5 groups, it is necessary to know which group of IKM is growing widely both in terms of the number of IKM, number of workers, investment value and production value. The aim of this research is to find out and analyze which small and medium industrial groups (IKM) are superior in Muaro Jambi district and help simplify the process of selecting superior SMEs in Muaro Jambi district. The analytical model used to determine priorities for leading small and medium industries in Muaro Jambi district is the SAW (Simple Additive Weighting) model. The SAW model is used to formulate a weighted sum of priorities for the performance ranking of each alternative on all attributes, while the system design method uses the System Prototyping method. The result of this research is the SPK system with the SAW model which shows that the leading small and medium industries in Muaro Jambi district selected based on predetermined criteria are the Chemical and Building Materials industry with a total of 0.813